PENGARUH PENGATURAN DEBIT INLET IPLC DENGAN PENURUNAN KADAR AMONIAK (NH3) PADA IPLC RSUD AJIBARANG KABUPATEN BANYUMAS TAHUN 2016 - Hendra Susanto; Agus Subagyo; Hari Rudijanto. IW (Buletin Keslingmas, 2017)
AbstractHospital liquid is the most potential resource of water pollution. The hospital wastes which containamoniac will cause several environmental problem such as eutrofikasi and an indication of organic mixturepollution which contain nitrogen. The goal of this research is to analizing the affect of IPLC RSUD Ajibarang. Inletdebit control with the decreation of amoniac rate at IPLC RSUD Ajibarang. The IPLC inlet debit control researchas 74,5 ltr/mnt, 68,5 ltr/mnt and 62,5 ltr/mnt. This kind of research is a pre eksperiment with pre and post testdesign approach. The collection of data been done by checking the amoniac rate of laboratory.The data presentedin table and structural narration. Data analization is using kruskal wallis statistik identification to identify thedifference of decreation amoniac rate with the control at inlet debit which is 74,5 ltr/mnt, 68,5 ltr/mnt and 62,5ltr/mnt.The result of the research gained is the rate amoniac IPLC RSUD Ajibarang with the control of inlet debitIPLC 74,5 ltr/mnt shown approximately 0,093 mg/ltr, inlet debit IPLC 68,5 ltr/mnt shown approximately0,075mg/ltr and inlet debit IPLC 62,5 ltr/mnt shown approximately0,050 mg/ltr. The edge point of amoniac is suitablewith the city regulation in Central Java Province No. 5 2012 at 0,1 mg/ltr. The test result is kruskal wallissignificant point at 0,000 0,05 (grade α) that lead Ho to an discharge of Ho or there is a decreation of amoniacrate with IPLC inlet debit control to IPLC RSUD Ajibarang liquid waste. Summarized by the researcherthat thereare significant decrease influence of amoniac rate at the control at IPLC RSUD Ajibarang inlet debit. The mosteffective to reduce amoniac rate is with the IPLC inlet debit 62,5 ltr/mnt. Suggested to the hospital’s Management toaccomplish the research result to reduce the amoniac rate in liquid waste